A novel contra-wound slow-wave structure for travelling-wave tube amplifier - Jha, Nilotpal (2014)
Backward-wave oscillation is frequently a problem in TWT amplifiers that use the conventional circular helix slow-wave structure (SWS). Circular contra-wound helix SWS, proposed in the past to solve this problem, is hard to fabricate at high frequencies. A planar version of the contra-wound structure is easily realizable but has not been studied so far.